Pengaruh Retribusi Pelayanan Pasar dan Pelayanan Parkir Terhadap Pendapatan Asli Daerah dengan Inflasi sebagai Moderasi - Diah Mulya Laksmi Leilani; Ika Wulandari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Original Regional Income is a component of regional revenue that reflects the extent to which a region is financially independent. A region is required to develop the revenue potential in its area. On the other hand, the phenomenon of regional insensitivity in recognizing cultural potential and actual resources is often found, which results in suboptimal Regional Original Income. This research aims to determine whether there is an influence of market service levies and parking service levies on local revenue with inflation as a moderation in Purworejo district. The population in this study is all district/city government data in Central Java for 2020-2022. The sampling technique used was a nonprobability sampling method with a purposive sampling technique and data from the Purworejo district government for 2020-2022 was selected as the sample. The data analysis method used is moderated regression analysis (MRA). The data that has been collected is then processed using the SPSS analysis tool. The research results show that market service levies have a positive effect on local original income with a significance value of 0.047 < 0.05. Parking service levies have a positive effect on local revenue with a significance value of 0.047 <0.05. Meanwhile, inflation does not moderate the influence of the relationship between market service levies on local original income with a significance value of 0.136. And inflation does not moderate the influence of the relationship between parking service fees and regional original income with a significance value of 0.239. This shows that if the income from market service levies and parking service levies is higher, then regional original income will also be higher, but if it is the opposite, then regional original income will also be lower, meanwhile inflation is unable to influence the rise and fall of market service levies and parking service levies on income. native to the region.